Design of an Adaptive Sidelobe Cancellation Algorithm for Radar. Issue 1 (February 2021) - Hong, Tian
Abstract: In complex electromagnetic interference environments, adaptive sidelobe cancellation is an effective measure to suppress radar active jamming. It adopts spatial filtering technology, which can effectively suppress sidelobe interference[1]. In this paper, the basic theory of adaptive sidelobe cancellation system is introduced, and two commonly used algorithms are briefly introduced. In practical application, the cancellation effect decreases due to many factors. In order to improve the performance of adaptive sidelobe cancellation, this paper proposes a method of adaptive acquisition of interference sampling data, and uses this method to simulate and analyze the collected jamming data. Now the device function is becoming more and more powerful, and the system hardware platform has also developed rapidly. Compared with the traditional method, this new interference data sampling method has certain advantages and is of practical significance. At the same time, the problems that should be paid attention to in engineering implementation are put forward.